Holistic Assessment of Calcium Fertilization in Potato: Diagnostic, Productivity, and Tuber Quality - Giletto, Claudia; Kloster Erreguerrena, M.; Ceroli, Paola Susana; Carciochi, Walter; Silva, Sandra; Rodríguez, Silvia; Salvagiotti, Fernando; Reussi Calvo, Nahuel Ignacio (Springer Nature, 2023)
Calcium (Ca) deficiency could negatively affect potato (Solanum tuberosum L.) tuber yield and quality. Therefore, it is required to develop Ca diagnostic methods and assess the impact of Ca fertilization on tuber yield and quality (dry matter and starch concentration, resistance to mechanical damage, and sensory texture attributes such as firmness, mealiness, granularity, and moisture). Field trials evaluating three Ca rates (0, 40, and 80 kg ha−1) were performed for six site-years. Soil exchangeable Ca (Cae) (0–20 cm) at planting and leaf Ca concentration (CaL) at tuber bulking were measured. At harvest, tuber yield, tuber quality parameters, and tuber Ca concentration (CaT) were determined. On average, across site-years, Ca fertilization increased tuber yield, CaT, and CaL by 16, 14, and 17%, respectively. Yield response to Ca increased 4.5 Mg ha−1 for each cmolc kg−1 reduction in soil Cae below 11.3 cmolc kg−1, while it increased 1.7 Mg ha−1 for each 0.1 g 100 g−1 reduction in CaL below 1.05 g 100 g−1. Calcium fertilization increased tuber dry matter (5%), starch (13%), and sensory texture attributes, mainly firmness (103%) and mealiness (70%). Also, these parameters were positively associated with CaT. The mechanical damage depth and mechanical damage index decreased with increments in Ca rate and CaT. Under Ca deficiencies, Ca fertilization is a recommended management practice for improving potato yield and quality while reducing tuber mechanical damage.